2017
DOI: 10.1186/s12936-017-1702-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of text-message reminders on paediatric malaria treatment adherence and their post-treatment return to health facilities in Kenya: a randomized controlled trial

Abstract: BackgroundShort Message Service (SMS) reminders have been suggested as a potential intervention for improving adherence to medications and health facility attendance.MethodsAn open-label, randomized, controlled trial to test the efficacy of automated SMS reminders in improving adherence to artemether–lumefantrine (AL) and post-treatment attendance in comparison with standard care was conducted at four health facilities in western Kenya. Children below five years of age with uncomplicated malaria were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…That study was based in a specific area and recommended further studies on health care promotion, intervention, and better communication regarding sustainable behavior changes [ 17 ]. Another study conducted in Kenya observing the efficacy of text-message reminders found that text-message reminders can increase a child’s compliance with respect to follow-up after anti-malarial treatment [ 18 ]. However, the effects of existing knowledge, attitude, and practices (KAP) of Kenyan populations with regard to malaria prevention strategies are rarely examined.…”
Section: Introductionmentioning
confidence: 99%
“…That study was based in a specific area and recommended further studies on health care promotion, intervention, and better communication regarding sustainable behavior changes [ 17 ]. Another study conducted in Kenya observing the efficacy of text-message reminders found that text-message reminders can increase a child’s compliance with respect to follow-up after anti-malarial treatment [ 18 ]. However, the effects of existing knowledge, attitude, and practices (KAP) of Kenyan populations with regard to malaria prevention strategies are rarely examined.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of approaches have been used to incorporate package inspection in the classification of adherence outcome [ 36 , 59 , 60 ]. Under trial conditions, blister packages have been retained and inspected with results successfully incorporated into the outcome measurement [ 61 ]. In other studies, package inspection has been included in the methods, but either excluded from the analysis [ 62 ], or not utilized altogether.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, examining the quality of treatment, including whether the correct number of tablets were given at the correct frequency for the correct number of days, may provide a more accurate picture of treatment adherence [ 35 , 37 , 59 , 63 , 66 ]. Recently studies measuring anti-malarial adherence have presented per-dose adherence measurements [ 36 , 59 , 61 ], this approach is useful as it can illustrate at which point patients stop taking their medications. However, this approach like those mentioned earlier relies on self-report, with or without package validation.…”
Section: Discussionmentioning
confidence: 99%
“…Results from trials using SMS to increase adherence to malaria treatment and to treatment for other diseases such as HIV and TB have shown mixed results [4750]. Content and type of messaging need to be well developed, tested and refined and locally adapted for their implementation to be successful [51, 52].…”
Section: Topic 4: Improving the Adherence To A Full Course Of Primaqumentioning
confidence: 99%